SPECTROSCOPIC ANALYSIS OF OSCILLATING ALGOL-TYPE SYSTEMS - Tkachenko, A.; Lehmann, H.; Tsymbal, V.; Mkrtichian, D. (Одеські астрономічні публікації, 2010)
We analyze time-series of highresolution spectra of RZCas, one of the brightest Algoltype stars where the primary shows δ Sct-like oscillations. Our inverstigation uses a variety of methods like the KOREL program to derive the orbital solution and to decompose the spectra of the binary components, the SynthV program to derive the elemental abundances of both components from the mean, decomposed spectra, and finally the newly developed Shellspec07_inverse program to compute optimized stellar parameters from the composite line profiles observed at different orbital phases including the eclipse mapping. Spectra of RZ Cas have been taken at two different epochs. In 2006, the system can be well modeled without including any Algol-typical effects like a gas stream or an accretion annulus into the calculations. We have only to assume that the secondary of RZCas shows a large dark spot on its surface pointing toward the primary, presumably originating from a cooling mechanism by the enthalpy transport via the inner Lagrangian point. The O-C residuals of our solution based on the spectra from 2001 show a complex distribution of circumbinary matter, however, pointing to the occurrence of an episode of rapid mass transfer. This assumption is supported by the deduced change of the orbital period of RZCas of 2 seconds between the two epochs of observations. Numerical simulations of the spatial filtration effect that occures during the primary eclipse showed that this effect can be used for an identification of the excited non-radial pulsation modes in terms of l and m numbers.